Influence of different nanoparticles embedded in crystalline carbon monoxide matrix on heat transfer in the nanocomposite - Nikonkov, R.V.; Stachowiak, P.; Jeżowski, A. (Физика низких температур, 2019)
The preliminary results of investigations of heat transfer in nanocomposites consisting of nanoparticles randomly distributed in solid carbon monoxide matrix are presented. In the experiment the thermal conductivity coefficient dependence on temperature for CO crystal with silica and palladium nanoparticles of different size embedded in the crystal structure was determined over the temperature range 2.2–35 K by steady-state heat flow
method. The results of the measurements were analyzed within the frame of relaxation time approximation. The
analysis shows that lowering of the thermal conductivity of the nanocomposites relative to pure carbon monoxide crystal observed for both types of the investigated nanoparticles, palladium and silica, is caused mostly by
scattering of phonons by boundaries of the nanoparticles. Additionally, the presence of the nanoinclusions promotes higher density of dislocations and influences the matrix lattice dynamics. Наведено попередні результати досліджень теплопереносу в нанокомпозитах, які містять наночастинки, що випадково розподілені у твердій матриці монооксиду вуглецю. Методом стаціонарного теплового потоку в температурному
інтервалі 2,2–35 К визначено експериментальні залежності
коефіцієнта теплопровідності від температури для кристалевого СО, що містить наночастинки оксиду кремнію та паладію різних розмірів. Результати вимірювань проаналізовано в
рамках апроксимації часу релаксації. Аналіз показує, що
зниження теплопровідності нанокомпозитів щодо чистого
кристала монооксиду вуглецю, яке спостерігається для досліджених наночастинок паладію та оксиду кремнію, обумовлено головним чином розсіюванням фононів на границях
наночастинок. Крім того, наявність нановключень сприяє
більш високій щільності дислокацій і впливає на динаміку
гратки матриці. Приведены предварительные результаты исследований
теплопереноса в нанокомпозитах, содержащих наночастицы,
случайным образом распределенные в твердой матрице монооксида углерода. Методом стационарного теплового потока в температурном интервале 2,2–35 К определены экспериментальные зависимости коэффициента теплопроводности
от температуры для кристаллического СО, содержащего внедренные наночастицы оксида кремния и палладия различных
размеров. Результаты измерений проанализированы в рамках
аппроксимации времени релаксации. Анализ показывает, что
понижение теплопроводности нанокомпозитов относительно
чистого кристалла монооксида углерода, наблюдаемое для
исследуемых наночастиц палладия и оксида кремния, обусловлено главным образом рассеянием фононов на границах
наночастиц. Кроме того, наличие нановключений способствует более высокой плотности дислокаций и влияет на динамику решетки матрицы.